Modelling a resilient yard template under storage demand fluctuations in a container terminal. Issue 9 (2nd September 2019) - He, Junliang; Tan, Caimao
ABSTRACT: This article investigates the generation of a resilient yard template, which has the property of resilience under storage demand fluctuations. A stochastic programming model is formulated aiming at minimizing the risk of containers without available storage slots being assigned in the designated area. Furthermore, a corresponding particle swarm optimization algorithm is proposed for solving the model. Finally, numerical experiments are conducted to verify the effectiveness of the proposed model and solution approaches.